Les représentations filmiques de Marie Stuart– Une femme de pouvoir dans l’air du temps - Armel Dubois-Nayt (Anglophonia)
This paper examines three cinematic portrayals of Mary Queen of Scots, the first by John Ford in 1936, the second by Charles Jarrott in 1972 and the last by Gillies MacKinnon in 2004. It starts by focusing on the way the Scottish Queen is depicted as a Catholic ruler who had to deal with the Scottish Reformation and the civil strife it entailed. These cinematic representations are considered in the wider scope of Marian myth-making as it developed in the sixteenth century with the aim of showing that until recently cinema has merely harped on the tropes found in her early modern detractors and defenders. This essay then moves on to argue that despite this reproduction of dated opinions, Mary Queen of Scots in these three films is an icon for the twentieth and twenty-first centuries. In the case of the first two films studied, it appears that she is used to illustrate the debates triggered by the women’s suffrage movement and the women’s liberation movement. In the third film, I contend that the characterization of the Queen of Scots is heavily influenced by the cultural phenomenon of the "girl power" that appeared in the mid-late 1990s. It is therefore only with the three waves of feminism in mind that one can fully comprehend how these films construct gender.